Ornamental Motifs in the Original Decoration of the ‘Vladychnaya’ Chamber in Novgorod - Tsarevskaya, Tatiana Iu. (Actual Problems of Theory and History of Art, 2021)
Painted in 1441 by the order of Archbishop Euthymius, the interiors of the Archbishop’s Chamber made an unforgettable impression on contemporaries, as evidenced by the testimony of the Athonite monk Pachomius Logothetes. But, did this decoration have a single conception, like the decoration of some structures in Western Europe, and what traditions could it be oriented towards? These questions are particularly acute due to the fact that the painting of the Chamber is the earliest among the few examples of painted decoration of civil buildings in medieval Russia. The remaining ornamental elements of the painting rediscovered during the restoration of 2006–2013 allow us to shed some light on these questions.The prevalence of plant motifs of the same type (“Blüttenblattstil”) in the decor (with the exception of braided rosettes) and an elaborate hierarchy in its distribution suggest that there is the personality of the master behind the unified concept of all the ornamental decorations of the Chamber. This master could have been familiar with samples of European decor and guided by them in the picturesque decoration of the rib arches. However, in the use of the ornamental motifs, he appealed to the local tradition. In this respect, the ensemble of the Archbishop’s Chamber appears to be a hybrid of two heterogeneous traditions.This publication has been completed with the support of the Russian Science Foundation (RSF), project № 18-18-00045 “Civil stone architecture of Novgorod (14th–15th centuries): a complex study”.
Keywords: ornament; ancient Russian art; monumental painting; fresco; medieval civil architecture; Archbishop Euthymius II